Driving towards Customer Purchase in Social Commerce: Harnessing the Significance of Content Marketing, Affiliate Marketing, and Customer Reviews - Subkhan, Farid; Ariesadewo, Adetya (Jurnal Administrasi Bisnis, 2026)
This study aims to understand the influence of content marketing, affiliate marketing, and customer review on consumer purchasing decisions through social commerce platforms. These platforms include social media channels that function as e-commerce such as TikTok Shop, Instagram Shop, Facebook Marketplace, Line Shop, YouTube Shop, and WhatsApp, The research employs a quantitative methodology, interviewing 200 respondents across five major cities in Indonesia: Jakarta, Surabaya, Bandung, Medan, and Semarang. The sample was selected using purposive sampling, targeting respondents aged 17 to 50 who actively shop through social commerce platforms. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The findings indicate that the most frequently used social commerce platforms in Indonesia are TikTok Shop (57.5%), Instagram Shop (18.5%), WhatsApp (10.5%), Facebook Marketplace (9.5%), and Line Shop (4%). The results of hypothesis testing reveal that while content marketing has a positive but statistically insignificant effect on purchasing decisions through social commerce, affiliate marketing, and customer reviews positively and significantly influence consumer purchasing decisions. These findings provide valuable insights for businesses leveraging social commerce, emphasizing the need to optimize the role of affiliate marketing and customer reviews to enhance online sales.